Quantitative determination of mineral matter in lignite by X-RAY spectrometry, using the Compton effect. - Perdikatsis, V. (Bulletin of the Geological Society of Greece, 2013)
For the evaluation of lignite quality, apart from the calorific value, it is necessary to determine the mineral phases, which are deposited simultaneously with the organic matter during the formation of peat or formed epigenetically during the coalification stages. The mineral matter content is usually expressed as ash, after the combustion of lignite, and its determination is a quite time consuming process. In this paper an attempt is made for a fast and easy quantitative determination of mineral matter in lignite samples with unknown concentrations, with the use of an X-ray spectrometer and in particular the Compton effect of the X-ray tube. The intensity of the Compton peak is a function of the mass absorption coefficient of the lignite sample, which in turn depends on the type and amount of the mineral matter contained. Using this property of the Compton Effect, the percentage of mineral matter of lignite was determined. The method was verified by analyzing lignites with known concentrations of inorganic mater. The results of this study showed, that the mineral matter content can be determined, by the proposed method, fast and accurately without lignite combustion.